MSDM Digitalization Strategy in Improving the Professionalism of Madrasah Ibtidaiyah Teachers: A Literature Study - Moh. Ali Fahmi; Moh. Rodiaminollah; Lu’lu’ Nurul Qomariyah; Abu Hasan (Global Education Journal, 2026)
Digital transformation in the education sector has driven fundamental changes in human resource management (HRM) practices, particularly in Islamic primary education institutions such as Madrasah Ibtidaiyah (MI). The digitalization of HRM is no longer limited to administrative efficiency but has evolved into a strategic instrument for enhancing teacher professionalism through data-driven management systems, digital performance evaluation, and continuous competency development. This study aims to analyze the concept of HRM digitalization strategies in the context of Madrasah Ibtidaiyah education and examine their role in improving teacher professionalism. This research employs a qualitative approach using a literature review method based on secondary data obtained from national scientific journals, academic books, and Indonesian education policy documents published within the last five years. Data were analyzed using content analysis, focusing on key themes such as HRM digitalization, teacher professionalism, and educational management transformation. The findings indicate that effective HRM digitalization strategies include the implementation of human resource information systems, e-performance systems, strengthening teachers’ digital literacy, technology-based competency development, and the transformation of digital organizational culture. HRM digitalization has been proven to enhance transparency, efficiency, accountability, and objectivity in teacher management. However, its success is strongly influenced by human resource readiness, educational leadership, and the availability of digital infrastructure. This study confirms that HRM digitalization plays a strategic role in developing sustainable teacher professionalism in Madrasah Ibtidaiyah through the integration of technology and the strengthening of digital pedagogical capacity.